The Impacts of Moisture Content on Performance and Emissions of a Four-Cylinder SI Engine Running with Fusel Oil-Gasoline Blends - Awad, Omar I.; R., Mamat; M. M., Noor; F., Yusop; I. M., Yusri (WSEAS, 2017)
Biofuels from Biomass are meant to decrease significantly dependence on fossil oil and reduce the environmental influences in energy use. Fusel oil one of biofuel that composed of a mixture of alcohols. Fusel oil obtained by-product during fermentation of agricultural products such as beet, cone, sweet molasses, grains, potatoes. According to the high research and motor octane rating also a high density of fusel oil compared with other fuels maybe it will get an essential place in the alternative. The main objective of this study was to determine the impacts of moisture on performance and emissions characteristics of a four-cylinder engine running with fusel oil-gasoline blends. The experiments were performed on spark ignition engine under 4500rpm engine speed, different engine loads and the different blending ratio of gasoline-fusel oil (G100, FBWE20, and FAWE20). In addition, the effects of test fuels upon brake power, brake thermal efficiency, brake specific fuel consumption, maximum in-cylinder pressure, and emissions (nitrogen oxide NOx, hydrocarbon HC, carbon monoxide CO, and carbon dioxide CO2) were examined. The heating value of fusel oil after water extracted (FAWE) become 33.8 MJ/kg that improved by 13% compared with original one (FBWE) 29.9 MJ/kg. Mostly at all blending of fusel oil–gasoline the brake power is slightly increased than that of gasoline. Also, the brake specific fuel consumption (BSFC) and thermal efficiency improved by reduced the water content of fuel oil. Furthermore, the NOx emission decreased with fusel oil-gasoline blends compared with pure gasoline at all engine loads. However, HC, CO, and CO2 emissions increased with fusel oil-gasoline blends. In general, the higher oxygen content and octane number of fusel oil with reducing water content led to improving the engine performance and NOx emission.